2005
DOI: 10.1051/0004-6361:20041566
|View full text |Cite
|
Sign up to set email alerts
|

Detecting cold H2globules in the outer Galactic disc by microlensing towards the Maffei 1 elliptical

Abstract: Abstract.A candidate source of dark matter in spiral galaxies is cold molecular hydrogen globules with a condensed central core and a disc-like space distribution probably similar to that of neutral hydrogen. This paper shows that the H 2 cores are sufficiently compact and massive to be detected by microlensing in the outer Galactic disc and that the Maffei 1 elliptical galaxy, at a distance of 3 Mpc and Galactic latitude b = −0.6 • , offers an ideal target for such an experiment. The microlensing optical dept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Grenier et al (2005) showed that much gas in the solar neighborhood is revealed only by γ-rays. Other indirect detections could be possible using micro-lensing events (Draine 1998;Fux 2005). However, this method has not been exploited up to now.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…Grenier et al (2005) showed that much gas in the solar neighborhood is revealed only by γ-rays. Other indirect detections could be possible using micro-lensing events (Draine 1998;Fux 2005). However, this method has not been exploited up to now.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%